Effects of Discontinuous Properties on the Stability of Tunnels - Nawarathna, T.H.K.; Kulathilake, L.K.N.S.; Perera, H.D.H.; Premalal, P.A.M.; Dharmaratne, P.G.R.; Chaminda, S.P.; Rohitha, L.P.S. (Department of Earth Resources Engineering, University of Moratuwa, 2010)
Main failures of underground openings during excavation are closely related to discontinuous properties of the surrounding rock mass and they affect differently to the stability of underground openings. In this research, attempts have been made to study the effect of discontinuities ever the rock mass stability with various infilling materials, dip angles and strikes by using laboratory scaled models. Specimens were casted using cement concrete mixture and five different dip angles (30°,45°,60°,75°,90°) and three infilling materials (quarry dust, kaolin and graphite) have been selected for the study. Models were tested to determine their uni-axial compressive strength. The results indicate that the dip angle of the joints and the orientation of the tunnel axis have significant impacts on the stability of the tunnel. The dip angle 90°, perpendicular to the tunnel axis shows a higher stability while the angle at 45°, shows the lowest stability. The tunnels excavated with axis parallel to the discontinuous plane should be avoided as much as possible. If it is unavoidable in any circumstances, well designed support system should be used. Types of infilling materials also affect the stability of the tunnel with graphite being the most unfavorable among the selected materials.
Keywords: Dip angle; Infilling; Strike; Tunnel axis